2020
DOI: 10.1109/access.2020.3029656
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Game-Based Approach for School-Enterprise Collaborative R&D Strategy on Digital Twin Technology

Abstract: Digital twin (DT) technology is an effective way to realize intelligent manufacturing, which has been increasingly received attention in both academia and industry. Thus, it is rather necessary and significant to collaboratively accomplish the research and development (R&D) of DT technology (RDDT). To explore a school-enterprise collaborative R&D strategy on DT technology, this paper proposes a differential game-based approach to compute the optimal R&D effort levels and optimal incomes of both parties in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…They found that the optimal knowledge-sharing amount and the optimal benefits in the centralized decisionmaking contract were both the highest. To explore optimal R & D strategies on digital twin technology, Guo et al [39] built a differential game in the school-enterprise system.…”
Section: Knowledge Sharing In University-industry Alliancesmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the optimal knowledge-sharing amount and the optimal benefits in the centralized decisionmaking contract were both the highest. To explore optimal R & D strategies on digital twin technology, Guo et al [39] built a differential game in the school-enterprise system.…”
Section: Knowledge Sharing In University-industry Alliancesmentioning
confidence: 99%
“…In addition, Yin et al [40] emphasized that the GTI level also affects revenue. Thus, considering the financial inputs from external institutions and government and drawing on the literature [39], we calculate the total revenue of the U-I as…”
Section: Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the diversity of the research data and the abstractness of the hypothetical variables, it is complicated to set up the initial value of the model by an actual assignment method based on realistic data. This paper refers to related works [ 55 , 56 ] and adopts the equilibrium assignment method (subjective assignment). The specific setting is shown in Table 5 .…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…The VSM is drawn based on the information from company’s ERP system and collected on-site. These data include the number of operators ( NO t ), the number of machines ( NM t ), cycle time ( C/T t ), shifts and the number of work in process [ work in progress (WIP) t ], etc (Guo et al , 2020d).…”
Section: Case Studymentioning
confidence: 99%